Relowering of Serum Na for Osmotic Demyelinating Syndrome - Hideomi Yamada; Koji Takano; Nobuhiro Ayuzawa; George Seki; Toshiro Fujita (Case Reports in Neurological Medicine)
We report a case in whom slow correction of hyponatremia (5 mmol/day for 3 days) induced central pontine myelinolysis (CPM). After the diagnosis was confirmed by imaging, we started to relower serum Na that completely recovered the sign and symptoms of CPM. Rapid correction of serum sodium is known to be associated with CPM. However, it may occur even after slow correction of hyponatremia. Currently, there is no standard therapy for CPM other than supportive therapy. Other therapy includes sterioid, plasmaphresis and IVIG, but these therapies have not been shown to be particularly effective. The pathophysiology of CPM is related to a relative dehydration of the brain during the correction of hyponatremia, resulting in cell death and demyelination, therefore gentle rehydration with lowering serum sodium may not be an unreasonable therapy. The present case provides supportive evidence that reinduction of hyponatremia is effective in treating CPM if started immediately after the diagnosis is suggested. The present case tells us that severe chronic hyponatremia must be managed with extreme care especially in patients with chronic debilitating illness and that relowering serum Na is a treatment of choice when CPM is suggested.